Integration of Collaborative and Individual Writing Strategies in the SPADA Model for IMRAD-Format Academic Writing - Abdul Wahid; Muhammad Dahlan (Jurnal Pendidikan dan Pengajaran, 2026)
Writing scientific articles using the IMRAD format has become a global standard in academic communication; however, university students in Indonesia still face various difficulties in mastering it, ranging from constructing arguments to maintaining consistency in academic style. This study aims to describe students’ responses to the implementation of the Collaborative Writing Strategy (CWS) and Individual Writing Strategy (IWS) integrated into the SPADA platform in the context of writing IMRAD-formatted scientific articles. This study employed a descriptive qualitative approach involving 60 students from the Indonesian Language and Literature Education and Elementary School Teacher Education programs. Data were collected through questionnaires, semi-structured interviews, and participatory observation. The analysis was conducted descriptively by emphasizing four main aspects: students’ experiences, perceived benefits, challenges, and understanding of scientific article writing. The results showed that the majority of students responded positively to the integration of CWS and IWS within SPADA. CWS was perceived to enhance students’ confidence in argumentation, critical thinking skills, and creativity, while IWS strengthened academic consistency, independence, and analytical skills. This study concludes that the implementation of SPADA is not only determined by technical readiness but also by pedagogical strategies and motivational support. The implications of this study contribute to the development of theories and practices in scientific writing instruction in the digital era. The integration of CWS and IWS through SPADA can be viewed as an innovative pedagogical strategy that strengthens students’ academic literacy while also enhancing the global competitiveness of higher education in Indonesia.